Household air pollution and childhood pneumonia in South Sudan: will clean cooking stoves reduce the incidence and mortality? - Gasim Omer Elkhalifa Abd-Elfarag; Charles O.C. Langoya (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2016)
Pneumonia causes more childhood deaths compared to other infectious diseases. Studies have showed that young children exposed to household air pollution (smoke) caused by burning of unprocessed solid fuels such as wood, charcoal, crop waste, animal dung and coal had double the risk of pneumonia infections compared to children who are not exposed or those from families using cleaner fuels such as electricity or gas. In 2012, more than half a million children below the age of 5 years died as a result of exposure to household air pollution worldwide. Based on studies which have indicated that reduction of household air pollution also reduces its health risks such as pneumonia, the World Health Organization recommended the use of cleaner fuels and/or technologies that offer significant health benefits, including the use of clean cooking stoves. Around 99% or all households in South Sudan use solid fuels for cooking in both rural and urban areas. This puts children in South Sudan at risk of pneumonia related deaths attributed to household air pollution. Therefore, promoting the use of clean/improved cook stoves such as the Uga Cooking Stove (locally made in Uganda, using charcoal) is critical to reduce the risk of childhood pneumonia and pneumonia related death in South Sudan.